Technology readiness for augmented reality integration in instructional design: Students’ perception - Trisnawati, Winda; Sulistiyo, Urip; Sofyan; Haryanto, Eddy (Indonesian Research Journal in Education |IRJE|, 2025)
This research aims to explore perception of students’ technology readiness in integrating instructional design based Augmented Reality (AR). This research was qualitative research. The technique of collecting data used interview technique. The sample of this research was 17 students who have used augmented reality in learning in English Education Study Program of Universitas Muhammadiyah Muara Bungo. The technique of data analysis used thematic analysis. Researchers used MAXQDA 24 software to analyze qualitative data. The findings showed that four positive and two negative perceptions of integrating AR. Positive perceptions include optimism, innovation, perceived usefulness, and ease of use. Students believe AR enhances English instruction and transforms teaching in a digital era. It also helps develop technical skills through user-friendly tools and pre-built assets, enabling content creation without advanced programming. Negative perceptions include discomfort and insecurity in AR use. Discomfort arises from technical issues like scanning difficulties, device overheating, image freezes, internet dependency, hardware limitations, high data consumption, and app instability. Insecurity stems from limited technical skills and challenges in conceptualizing AR designs.